Banyāi sarup Čhangwat N̜ōng Khāi (Fāi Kh̨ōmūn læ Tittām Pram̄œn Phon, Samnakngān Čhangwat N̜ōng Khāi, 1990)
Summary report on economic and social conditions of Nong Khai Province, Northeastern Thailand.